Sexually transmitted infections in an African migrant population in Portugal: a base-line study - Luis Távora-Tavira; Rosa Teodósio; Jorge Seixas; Emília Prieto; Rita Castro; Filomena Exposto; Jorge Atouguia (Journal of Infection in Developing Countries)
Background: For geographical and recent historic reasons, Portugal is a gateway and home for immigration from sub-Saharan countries. Misconceptions related to these populations often lead to consider them as high-frequency clusters for dissemination of sexually transmitted infections (STIs). Epidemiological evidence-based data is needed to elucidate these issues and baseline prevalence studies are the starting point for this. Methodology: A prospective study was conducted in 220 African migrants (171 men and 49 women), recently arrived in Portugal, at the time of their first consultation. The presence of STIs was evaluated using a clinical syndromic approach and biological confirmation for gonorrhoea, Chlamydia trachomatis genital infection, syphilis, Hepatitis B and Human Immunodeficiency Virus (HIV) infection. Results: Global prevalence of the targeted infections were 1.8% for gonorrhoea, 0 % for Chlamydia infection, 4.1% for Syphilis, 5.9% for HBsAg presence and 7.3% for HIV infection. Globally, 16.4% of the studied persons had at least one sexually transmitted infection. Conclusions: We concluded that prevalence rates encountered in this population is similar to that of non-migrant Portuguese populations with a high risk for sexually transmitted diseases. Therefore migration from sub-Saharan Africa doesn’t seem to constitute a particularly critical isolated factor for public health risk of STIs in the community.